Design and analysis of a compact flexure-based precision pure rotation stage without actuator redundancy. (November 2016) - Clark, Leon; Shirinzadeh, Bijan; Zhong, Yongmin; Tian, Yanling; Zhang, Dawei
Abstract: This paper presents the mechanical design, optimisation, and computational and experimental analyses of a flexure-based single degree of freedom rotation stage. The mechanism possesses a rotationally symmetric configuration, whilst only employing a single piezoelectric actuator, which increases the mechanism's ability to reject cross-coupled drift of the rotation centre. This layout is facilitated by a novel multi-level structure, which exploits emerging additive manufacturing techniques for its construction, and is compact, with little unused volume. Computational analysis has been employed for both the optimisation of the mechanism, to increase its workspace whilst maintaining a small physical footprint, and subsequently to predict its performance. The cross-coupled drift, particularly its variation with respect to assembly and manufacturing errors, is explored in depth. A prototype has been manufactured, which fits within a 128mm×153mm×30mm bounding box, and its working range has been experimentally determined to be 2.540mrad, with a first natural frequency of 175.3Hz. Highlights: A flexure-based single degree of freedom rotation stage is proposed. The rotationally symmetric design minimises cross-coupled output motions. A two-level structure is used, allowing a single actuator and preventing redundancy. The mechanism's behaviour, particularly cross-coupled drift, is analysed extensively. An experimental prototype is made to verify the workspace and computational results.